First case report of a vertebral osteomyelitis caused by carbapenem-resistant Enterobacter cloacae treated with imipenem/cilastatin/relebactam prolonged infusion then meropenem/vaborbactam in continuous infusion - Laffont-Lozes, Paul; Naciri, Tayma; Pantel, Alix; Martin, Aurélie; Pruvot-Occean, Anne-Sophie; Haignere, Vincent; Loubet, Paul; Sotto, Albert; Larcher, Romaric (Frontiers in Pharmacology, 2024)
Introduction: Bone and joint infections (BJIs) caused by multidrug-resistant bacteria are becoming more frequent. However, data on the use of novel β-lactam/β-lactamase inhibitors, such as imipenem/cilastatin/relebactam (I-R) and meropenem/vaborbactam (MVB), to treat BJIs is lacking. Furthermore, prolonged infusions of these β-lactams should theoretically optimize pharmacokinetic/pharmacodynamics target in these indications, but there are currently no reports on this type of infusions, especially in the setting of BJI. a mis en forme : Anglais (Royaume-Uni) a mis en forme : Police :Italique, Anglais (Royaume-Uni) a mis en forme : Anglais (Royaume-Uni) a mis en forme : Français (France) a mis en forme : Anglais (Royaume-Uni) a mis en forme : Anglais (Royaume-Uni) a mis en forme : Français (France) a mis en forme : Anglais (Royaume-Uni) a mis en forme : Français (France) a mis en forme : Anglais (Royaume-Uni) Case presentation: We report a case of a vertebral osteomyelitis caused by carbapenem-resistant Enterobacter cloacae successfully treated with extended-infusion of I-R (1.25 g q6h over 2h), then with continuous infusion of MVB (2g q4h as over 4h). Therapeutic drug monitoring confirmed that extended-infusion of I-R and continuous infusion of MVB achieved serum concentrations up to 12 mg/L of imipenem and 19 mg/L of meropenem, respectively.The favorablefavourable outcome of this patient treated for a vertebral osteomyelitis caused by carbapenem-resistant E. . cloacae suggest that extended-and continuous infusions of I-R and MVB, are promising regimens for treatment of BJIs caused by carbapenem-resistant Enterobacterales.